سيميائية العتبات النصية في رواية وعد الياسمين لرابح فيلالي - بلقاسم, بشرى (جامعة الوادي - university of Eloued, 2020)
تروم دراستنا النقدية إلى إماطة اللّثام عن تجليَّات الوطن وتمثّلاته التي أسقطها الروائيّ في ثنايا الرواية ، ومحاولة استقطاب أبعادها الجمالية عبر أسداف الدلالات الرمزية للعتبات والنصوص الموازية ،واستثارة إيحاءاتها ومعطياتها المشحونة بسوداوية الواقع المتصدّع. Our monetary study aims at revealing the manifestations of the homeland and its implications, which the novelist dropped in the folds of the novel, and attempts to attract its aesthetic dimensions through the symbolic indications of thresholds and parallel texts, and to evoke their inspirations and facts, which are charged with the rudeness of reality.
Semiotics of textual thresholds in the novel promised the jasmine Rabah Filali
مقال
Keywords: الوطن ; العتبات ; العنوان; وعد الياسمين ; رابح فيلالي; The homeland, Thresholds,title , the promise of jasmine , Rabah Filali.